An Analysis of EFL Students' Communication Strategies in Classroom Context - Azis, Andi Herlymerdania Mutia; Rum, Eka Prabawati; Mahmudah, Dzur Rif’ah (Journal of Language Testing and Assessment, 2023)
This study aims to find out the types of communication strategies used by EFL students when learning English in the 12th grade English Cross Interest class at SMAN 5 Bantaeng. This study used descriptive qualitative method, data were collected through observation and interviews conducted with 4 students. Data came from three sources: namely audio recordings of naturally occurring classroom interactions; interviews with students and observation notes taken in the classroom. Data from the interaction transcripts were examined using Dorney & Scott's (1997) taxonomy of communication strategies.The results of this study show that there are five types of communication strategies that most often appear when students communicate with their interlocutors as well as towards their teachers during learning activities, namely; Message Abandonment, Non-Linguistic Means, Filler, Appeal For Help and Asking For Clarification. The students used L1 because the students found it difficult to understand L2. This is due to the fact that students lack knowledge of English. Students experience these types of communication strategies due to thinking time, anxiety, lack of focus, nervousness, doubt, lack of knowledge, lack of vocabulary, grammatical errors and self-confidence.